2020
DOI: 10.1049/mnl.2019.0414
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of fabrication of Ni‐graphene composite: temperature effect

Abstract: Fabrication of Ni-graphene composite by hydrostatic pressure at finite temperatures or by the subsequent annealing is studied by molecular dynamics simulation. Crumpled graphenethe network of folded and crumpled graphene flakes connected by van-der-Waals bondsis chosen as the matrix for Ni nanoclusters. It is found that hydrostatic compression at zero or room temperature cannot lead to the formation of the composite structure. Even strongly compressed crumpled graphene after unloading returned to the initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
(77 reference statements)
0
15
0
1
Order By: Relevance
“…The initial structure is compressed at 1000 K to obtain graphene–nickel composite material (c, c’). Composite can be fabricated under hydrostatic compression at high temperatures [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial structure is compressed at 1000 K to obtain graphene–nickel composite material (c, c’). Composite can be fabricated under hydrostatic compression at high temperatures [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the other approach to obtain the Ni-graphene composite was applied: introducing metal nanoparticles to the crumpled graphene matrix. In [ 41 , 42 , 43 , 44 ] it was shown that such composites can be obtained through compression combined with high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between loading and unloading stress–strain curves reveals that this is completely non-elastic media. The important advantage that such a morphology of the crumpled graphene structure capable of absorbing large amounts of other atoms in its cavities, which was shown in our previous works [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 83%
“…However, these pores quickly disappeared during compression. It should be mentioned that an increase in the size of the computation cell by two times did not lead to significant changes in the results [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation